One pot chemo/enzymatic synthesis of chiral δ-substituent caprolactam and its configuration controlling(手性δ-取代己内酰胺化学/酶串联一锅法合成及立体构型调控) - 屠美玲(TU Meiling); 王祁宁(WANG Qining); 李琰君(LI Yanjun); 张建庭(ZHANG Jianting); 贾继宁(JIA Jining); 杨阿三(YANG Asan) (Zhejiang Daxue xuebao. Lixue ban, 2024)
Herein, a novel one pot synthesis of chiral δ-substituent caprolactam strategy which applies 1-substituent homoallylic amine as the starting material is reported. This method combines the enzymatic dynamic kinetic resolution (DKR) and ring cross metathesis. Moreover, the configuration of caprolactam can be controlled by using lipase and protease as the DKR catalyst. The enantiomeric excess value of obtained R- and S-caprolactam can reach up to 90% and 82%, the yield can also be above 82% and 70%.(报道了一种以1-取代高烯丙基胺为原料，结合酶催化动态动力学拆分与分子内烯烃复分解反应串联一锅法制备手性δ-取代己内酰胺的方法。分别用脂肪酶和蛋白酶作为动态动力学拆分催化剂，实现了手性δ-取代己内酰胺立体构型的调控。通过该方法制备的R-δ-取代己内酰胺的对映体过量值（enantiomeric excess，ee）均在90%以上，产率维持在76%以上；所制备的S-δ-取代己内酰胺的ee也在82%以上，产率均高于70%。)